2006
DOI: 10.1007/s00436-005-0104-9
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in a holoendemic area of Burkina Faso: a cross-sectional study

Abstract: A malaria survey of the entire population of a village in Western Burkina Faso (n=1,561) was conducted to assess malaria endemicity. The study population was examined for symptoms characteristic of malaria including fever, anaemia, splenomegaly and parasites present in thick blood films. In the overall study population, the prevalence of Plasmodium spp. infection by microscopic examination of thick blood films was 79.0% (1,233/1,561). In a subcohort with 201 individuals, PCR techniques found a prevalence rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…In 2007, when transmission was highest, several well established risk factors correlated with infection, including younger age [23], presence of anaemia [24], using open water sources [4], sleeping without a bed net [3-5,8], rainy season [5,7], and self-reported or documented symptoms [2]. However, in 2008 and 2009, when the prevalence of malaria was substantially lower, only self-reported or documented fever correlated with infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, when transmission was highest, several well established risk factors correlated with infection, including younger age [23], presence of anaemia [24], using open water sources [4], sleeping without a bed net [3-5,8], rainy season [5,7], and self-reported or documented symptoms [2]. However, in 2008 and 2009, when the prevalence of malaria was substantially lower, only self-reported or documented fever correlated with infection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous prior studies identified individual-level risk factors for malaria, but many were conducted in areas of high endemicity [2] and among high-risk groups, such as children [3-5] and pregnant women [6,7]. However, in regions with declining malaria transmission as a result of accelerated control efforts, these well-characterized, individual-level risk factors for malaria may not be valid [8].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria is a frequent cause of clinically apparent anemia in Nouna and infection with Plasmodium species is highly prevalent after the rainy season (approximately 80% as detected by microscopic examination of thick blood films and more than 90% by PCR techniques) [12]. The persistence of submicroscopic Plasmodium gametocyte carriage which has been shown to be common in an area of low and seasonal transmission [13] may lead to increased hemolysis and clearance of uninfected erythrocytes and have also have a negative impact on hematopoesis [14].…”
Section: Resultsmentioning
confidence: 99%
“…The complete details of the protocol of each study have been described elsewhere (17, 18, 2628) and shorter summaries are presented here. Briefly, the ITN study was a randomized controlled trial to assess the long-term effects of ITN protection during early infancy among 3,387 children from 41 villages in CRSN (27).…”
Section: Methodsmentioning
confidence: 99%
“…The Environment and Weather Malaria (EWM) study was an observational study among 867 children to determine the prevalence of malaria among the cohort children, the incidence of malaria, and the effect of temperature, rainfall, and relative humidity on Plasmodium falciparum infection risk (18). The Bourasso study was a cross-sectional study to evaluate the prevalence of malaria infections, chloroquine related resistance, and proportion of moderate to severe anemia in all residents of Bourasso village (including 355 children) near Nouna, Burkina Faso (28).…”
Section: Methodsmentioning
confidence: 99%